Distinguishing Human Creativity from AI-Generated Literary Texts - Jasim, Yaser A.; Awqati, Ali Jala (PROSPECTIVE RESEARCHES, 2025)
Artificial intelligence (AI) technology has grown rapidly and authors can write paragraphs and sentences that accept such acts to human compositions, scholars have been examining the differences between computer-generated works and those written by humans. This review is an analysis and combination of papers that do a comparative study of contemporary literature by human and artificial intelligence. Theoretical techniques such as formal language, structure style, and narration are used in the study to make comparisons between human writing features and AI text patterns. While AI systems can reproduce certain essential aspects of literature in text, they capture a limit in producing new content and comprehensive ideas expressed in language. The problem statement of the research consists of describing scientific intervals in the separation of AI substance from human creativity, as well as philosophical, cultural, and ethical issues of AI in the literary context. Current research has been identified as having suffered from significant weaknesses in matters of complicated literary consistency and literary relations between authors and cultural knowledge. The study concludes that collaborative research methodology and critical self-evaluation are necessary because AI transforms how individuals make and analyze literature.